2015
DOI: 10.1017/s1751731115001275
|View full text |Cite
|
Sign up to set email alerts
|

Effect of locomotion score on sows’ performances in a feed reward collection test

Abstract: Sows housed in groups have to move through their pen to fulfil their behavioural and physiological needs such as feeding and resting. In addition to causing pain and discomfort, lameness may restrict the ability of sows to fulfil such needs. The aim of our study was to investigate the extent to which the mobility of sows is affected by different degrees of lameness. Mobility was measured as the sow's willingness or capability to cover distances. Feed-restricted hybrid sows with different gait scores were subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…For lameness, no unequivocal cut-off between “lame” and “non-lame” can yet be determined, as some authors consider that some changes in the locomotion pattern (e.g., stiffness) might not result in discomfort or pain [ 66 ; 68 ] and therefore should not be considered as lame. In the present study we used a cut-off based on the lameness score at which sows became less willing to walk to obtain a highly tempting reward [ 45 ]. Using the mean locomotion score allowed us to describe the severity of lameness in a more nuanced way than classifying sows simply as lame vs. non-lame.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For lameness, no unequivocal cut-off between “lame” and “non-lame” can yet be determined, as some authors consider that some changes in the locomotion pattern (e.g., stiffness) might not result in discomfort or pain [ 66 ; 68 ] and therefore should not be considered as lame. In the present study we used a cut-off based on the lameness score at which sows became less willing to walk to obtain a highly tempting reward [ 45 ]. Using the mean locomotion score allowed us to describe the severity of lameness in a more nuanced way than classifying sows simply as lame vs. non-lame.…”
Section: Discussionmentioning
confidence: 99%
“…Locomotion of sows was analyzed as mean locomotion score, lameness prevalence and lameness incidence. For estimating lameness prevalence, sows were considered lame when their locomotion score was >60 mm on the tVAS [ 45 ]. For estimating lameness incidence, a new case of lameness was defined as a previously non-lame sow (<60mm on tVAS) that had become lame (>60mm) and for which the locomotion score had increased by >30 mm since the previous score.…”
Section: Methodsmentioning
confidence: 99%
“…Subjective scores are prone to poor reliability (125), and one study showed poorer interobserver agreement at the lower end of the lameness scale (126). For example, no difference in motivation to obtain a food reward was detected between mildly lame and non-lame sows (113). However, it is possible that pigs may conceal signs of mild pain more easily than signs of severe lameness-pain, which could be advantageous in relation to access to resources.…”
Section: Pain Assessment In Pigsmentioning
confidence: 99%
“…Food consumption decreased after thoracotomy surgery in pigs (110), and time spent feeding has been used to assess the efficacy of pain mitigation strategies in pigs undergoing abdominal surgery (111) and a femoral fracture model (112). In a study using a feed reward collection test to assess sows’ motivation to obtain feed rewards with different levels of lameness, moderately and severely lame sows obtained fewer rewards than mildly and non-lame sows (113). Unexpectedly, tail-bitten pigs, which had been given ketoprofen, spent less time at the feeder compared with those given a saline placebo (114).…”
Section: Pain Assessment In Pigsmentioning
confidence: 99%
See 1 more Smart Citation